A novel variant in the DSE gene leads to Ehlers–Danlos musculocontractural type 2 in a Pakistani family. (13th July 2021) - Ullah, Ikram; Aamir, Muhammad; Ilyas, Muhammad; Ahmed, Akmal; Jelani, Musharraf; Ullah, Wahid; Abbas, Muhammad; Ishfaq, Muhammad; Ali, Fawad; Yip, Janice; Efthymiou, Stephanie; Ahmed, Habib; et al.
Abstract: The Ehlers–Danlos syndrome (EDS) is a group of heritable connective tissue disorders. Common features of EDS include skin hyperextensibility, articular hypermobility, and tissue fragility. It is classified into 13 subtypes, caused by variations of more than 19 different genes. Among these two subtypes, EDS musculocontractural type 1 (EDSMC1/mcEDS‐ CHST14 ; MIM# 601776) is caused by biallelic mutations in the CHST14 gene (MIM# 608429) on chromosome 15q14 and EDS musculocontractural type 2 (EDSMC2/mcEDS‐ DSE ;MIM#615539) is caused by a mutation in DSE (MIM# 605942) on chromosome 6q22. In this study, clinical and molecular diagnoses have been performed for a consanguineous Pakistani (Pakhtun) family with five affected siblings, presenting mcEDS‐ DSE phenotype. Whole‐exome sequencing analysis identified a novel homozygous DSE variant (NM_001080976.1; c.2813T>A, p.Val938Asp) in the proband. Sanger sequencing in all available affected members and their obligate carriers confirmed autosomal recessive segregation of the diseased allele. To the best of our knowledge, this variant identified is novel and expands the DSE pathogenicity leading to EDS, musculocontractural type 2. The result obtained has the potential to help in early diagnosis, genetic counseling, and possible therapeutic inventions.